Commitment, Discipline, and Work Environment on Job Satisfaction and Teacher Performance at SMK Negeri Tambusai Utara, Rokan Hulu District - Rizaldi Putra; Sudarno Sudarno; Joko Sutanto; Mukhsin Mukhsin; Suyono Suyono (International Conference on Business Management and Accounting, 2023)
The purpose of this study was to determine and analyze the effect of organizational commitment, work discipline and work environment on job satisfaction and teacher performance at SMK Negeri Tambusai Utara, Rokan Hulu. The sampling technique used in this study used a sample in which all members of the population became the sample, as many as 78 people became the sample. The data analysis technique in this study used descriptive analysis and the Equation Structure Model (SEM) PLS with the help of Smart PLS software. The results of this study indicate that commitment and work discipline are not significant on job satisfaction. The work environment is significantly positive on job satisfaction. Organizational commitment and work discipline are significant to performance. Environment and job satisfaction are not significant to performance. For further writers can add other independent factors that can affect teacher job satisfaction and teacher performance. Both internal factors that exist at school and factors outside of school.